Reducing prescribing of benzodiazepines in older adults: a comparison of four physician-focused interventions by a medical regulatory authority - Ashworth, Nigel (BMC Fam Pract, 2021)
BACKGROUND: The inappropriate and/or high prescribing of benzodiazepine and ‘Z’ drugs (BDZ +) is a major health concern. The purpose of this study was to determine whether physician or pharmacist led interventions or a simple letter or a personalized prescribing report from a medical regulatory authority (MRA) was the most effective intervention for reducing BDZ + prescribing by physicians to patients 65 years of age or older. METHODS: This was a four-armed, one year, blinded, randomized, parallel-group, investigational trial in Alberta, Canada. Participants were fully licensed physicians (n = 272) who had prescribed 4 times the defined daily dose (4 + DDD) or more of any BDZ + to an older patient at least once in the 3(rd) quarter of 2016. All physician-participants were sent a personalized prescribing profile by the MRA. They were then randomized into four groups that received either nothing more, an additional personal warning letter from the MRA, a personal phone call from an MRA pharmacist or a personal phone call from an MRA physician. The main outcomes were prescribing behavior change of physicians at one year in terms of: change in mean number of older patients receiving 4 + DDD BDZ + and mean dose BDZ + prescribed per physician. To adjust for multiple statistical testing, we used MANCOVA to test both main outcome measures simultaneously by group whilst controlling for any baseline differences. RESULTS: All groups experienced a significant fall in the total number of older patients receiving 4 + DDD of BDZ + by about 50% (range 43–54%) per physician at one year, and a fall in the mean dose of BDZ + prescribed of about 13% (range 10–16%). However, there was no significant difference between each group. CONCLUSIONS: A personalized prescribing report alone sent from the MRA appears to be an effective intervention for reducing very high levels of BDZ + prescribing in older patients. Additional interventions by a pharmacist or physician did not result in additional benefit. The intervention needs to be tested further on a more general population of physicians, prescribing less extreme doses of BDZ + and that looks at more clinical and healthcare utilization outcomes. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12875-021-01415-x.